Motivational Factors that Influence Foreign Direct Investment in Kurdistan Region - Rahim Jafar Mahammad Sharif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research examines the motivational factors that influence foreign direct investment in the location of Kurdistan Region. Market factors, in the past, have been a dominant motivation in choosing a location for investment. Political stability of the host location has also been a factor. Political stability refers to the characteristics of a country that provide Kurdistan Region. Firms with a sense of security, such as a consistent legal system and a stable government friendly to the Kurdistan Region. I aim to answer the above research questions and find out what Factors Have Affected the Rise of FDI in Kurdistan. I would also bring forward an overall understanding of how Kurdistan has transformed and how the different sectors have been affected due to FDI. It is not only the economy, politics and social status of Kurdistan that affects FDI, but FDI also has as big an impact of these three areas.This study selects a sample of 3 cities to investigate the location choice of FDI in Kurdistan Region. Those 3 cities cover the most major cities in the Kurdistan Region. To minimize the impact of outliers or extreme effects, this study mainly selects major cities in every province. This practice is undertaken in the following multiple regression analyses and by comparing coefficient estimates from different specifications, no clear sign of multicollinearity is found. Also it should be noted that although multicollinearity may ‘mask’ the true relationship between dependent and independent variables, it does not bias the results nor affect the fitness of the model. FDI would not be able to succeed in any nations without the attendance of necessary factors, which have been explained as determinants of FDI in the structure of the research. One of the main factors to rich the concentration of outer investors is suitable genesis means.